Analysis of the Digital Readiness Map for Organisational Zakat Management in Optimising Fundraising Efforts: Best Practices from Indonesia - Yurista, Dina Yustisi; Mahanani, Setyo; Arifandi, Firman; Riyani, Anggita Yayang; Achmad, Noor (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2025)
In the era of rapid technological advancement, zakat management organisations (OPZ) encounter both opportunities and challenges in optimising digital transformation to enhance the efficiency, transparency, and reach of zakat fund collection. This study aims to assess the digital readiness level of OPZ in Central Java, Indonesia, through the development and application of the Digital Zakat Readiness Index (IKDZ), a quantitative instrument that evaluates four key dimensions: digital infrastructure, utilisation of digital tools, digital ecosystem and culture, and human resource capabilities. Employing a mixed-methods approach that combines quantitative calculations with qualitative assessment, data were collected from ten OPZs using structured questionnaires. The findings reveal an average IKDZ score of 0.619, categorising OPZs within the “technology development readiness” classification; however, disparities persist, particularly regarding the quality and availability of human resources. The study also incorporates an Islamic legal (fiqh) perspective, confirming that digitalisation is permissible (mubah) as a means to support the benefits and objectives of zakat in alignment with maqashid sharia. This research provides a strategic contribution for zakat institutions to enhance their digital capabilities, align technology use with sharia principles, and foster inclusive digital ecosystems for effective zakat management. Further research is recommended to broaden the regional scope and investigate the relationship between levels of digitalisation and zakat fundraising performance.